Five-phase switched reluctance motor: design and performance - Green,TC; Khater,MM; Williams,BW; El-Shanawany,MM; Hassanein,AA (1994)
This paper presents a design and experimental results for a five-phase switched reluctance motor drive. The system improves SR drive performance by increasing the number of phases without increasing the number of switching devices. A comparison is made of the torque speed characteristics of the motor when fed from the proposed converter and a asymmetric half bridge. This study shows that the proposed converter matches the conventional converter over a very wide speed range.